2022
DOI: 10.1039/d1fo03405g
|View full text |Cite
|
Sign up to set email alerts
|

Large-leaf yellow tea attenuates high glucose-induced vascular endothelial cell injury by up-regulating autophagy and down-regulating oxidative stress

Abstract: Vascular endothelial cells injury induced by high glucose (HG) plays an important role in the occurrence and development of diabetic vascular complications. Yellow tea has a protective effect on vascular...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…[7][8][9][10] The most important green tea constituents are catechins, a group of bioactive polyphenols. [11][12][13][14][15][16] Although several studies have described the antiaging effects of tea extract, [17][18][19][20][21] antiaging studies on tea components mostly focus on the major catechin, (−)-epigallocatechin gallate (EGCG). Nevertheless, these studies, which only produced mediocre antiaging results, have limited our understanding of the antiaging effects and the underlying material basis of green tea.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] The most important green tea constituents are catechins, a group of bioactive polyphenols. [11][12][13][14][15][16] Although several studies have described the antiaging effects of tea extract, [17][18][19][20][21] antiaging studies on tea components mostly focus on the major catechin, (−)-epigallocatechin gallate (EGCG). Nevertheless, these studies, which only produced mediocre antiaging results, have limited our understanding of the antiaging effects and the underlying material basis of green tea.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a study reported that the protein level of p‐p70S6K, a mTORC1 downstream molecule, is elevated in the HG environment (Fan et al, 2017). In our previous study, upregulating the AMPK/mTOR signaling pathway could enhance autophagy via the AMPK‐dependent pathway in HG‐treated HUVECs (Wang et al, 2022). Our results are consistent with those of previous studies which reported that the protein expression levels of p‐mTOR and p‐p70S6K is increased and mTOR is activated in HG‐treated HUVECs.…”
Section: Discussionmentioning
confidence: 91%
“…Long‐term hyperglycaemia in diabetes can cause various cardiovascular diseases, such as atherosclerosis and cardiac hypertrophy. Vascular endothelial injury is the main factor in the development of diabetic vascular complications (Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to research new applications of tea flowers for improving the economic value thereof. Large-leaf yellow tea (LYT) is one kind of yellow-type tea which has multiple health benefits, such as alleviating alcoholic liver disease and inhibiting adipose tissue hypertrophy ( Xu et al., 2021 ; Wang et al., 2022 ; Wu et al., 2022 ). However, LYT is made from old tea leaves and stems, leading to poor aroma and flavor or being unpopular.…”
Section: Resultsmentioning
confidence: 99%
“…In tea flowers, the abundance of volatiles, particularly the terpenoid compounds, was detected. Then, we analyzed the terpenoid biosynthesis in flowers, and the transcriptome data of developing leaves and stems was used for comparison as control, which was generated by our previous study (Zhang et al, 2022). Most early genes involved in terpenoid biosynthesis showed low expression levels in F1, then increased in F2 and F3, and then kept a high level in opening flowers (Supplementary Table S3).…”
Section: Tea Flowers Expressed Terpenoid Biosynthesis Genes For Diver...mentioning
confidence: 99%